2018
DOI: 10.1038/s41418-018-0169-5
|View full text |Cite
|
Sign up to set email alerts
|

TRIM17 and TRIM28 antagonistically regulate the ubiquitination and anti-apoptotic activity of BCL2A1

Abstract: BCL2A1 is an anti-apoptotic member of the BCL-2 family that contributes to chemoresistance in a subset of tumors. BCL2A1 has a short half-life due to its constitutive processing by the ubiquitin-proteasome system. This constitutes a major tumor-suppressor mechanism regulating BCL2A1 function. However, the enzymes involved in the regulation of BCL2A1 protein stability are currently unknown. Here, we provide the first insight into the regulation of BCL2A1 ubiquitination. We present evidence that TRIM28 is an E3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
42
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(49 citation statements)
references
References 65 publications
5
42
0
Order By: Relevance
“…Indeed, we show here that Trim17 and Trim39 physically interact with each other. In a similar way, we have previously shown that TRIM17 inhibits the activity of two other TRIM proteins to which it is able to bind: TRIM41 (Iréna Lassot et al, 2018) and TRIM28 (Lionnard et al, 2019). It is interesting to note that TRIM39 and TRIM41 are very close from a phylogenetic point of view (Qiu et al, 2020;Sardiello et al, 2008), suggesting that common mechanisms could be involved in their inhibition by Trim17.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Indeed, we show here that Trim17 and Trim39 physically interact with each other. In a similar way, we have previously shown that TRIM17 inhibits the activity of two other TRIM proteins to which it is able to bind: TRIM41 (Iréna Lassot et al, 2018) and TRIM28 (Lionnard et al, 2019). It is interesting to note that TRIM39 and TRIM41 are very close from a phylogenetic point of view (Qiu et al, 2020;Sardiello et al, 2008), suggesting that common mechanisms could be involved in their inhibition by Trim17.…”
Section: Discussionsupporting
confidence: 60%
“…On the contrary, overexpression of Trim17 reduces the ubiquitination of NFATc3 and increases its steady-state protein level (Mojsa et al, 2015). Since TRIM17 can prevent ubiquitination of some of its binding partners by inhibiting other E3 ubiquitin-ligases from the TRIM family (Iréna Lassot et al, 2018;Lionnard et al, 2019), we hypothesized that the stability of NFATc3 might be regulated by a TRIM protein interacting with Trim17, such as Trim39.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, in NB Neuro2A cells, TRIM17 mediates the ubiquitination and degradation of Mcl-1, an anti-apoptotic Bcl-2 family protein that is necessary for initiating neuronal apoptosis [50]. TRIM17 has also been reported to stabilize BCL2A1, another anti-apoptotic Bcl-2 family protein that contributes to chemo-resistance in a subset of tumors [51]. In summary, these results suggest that TRIM17 is an important factor in neuronal apoptosis.…”
Section: Trim17mentioning
confidence: 89%
“…Repressing apoptosis by stabilizing anti-apoptotic proteins Mcl-1 [51,52] TRIM32 Enhancing transcriptional activity of RARα [63] Inducing asymmetric cell division (ACD) [64] Facilitating c-MYC and n-MYC proteasomal degradation [62,64] TRIM36 Being hypermethylated in neuroblastoma tumors [72] TRIM59 Inducing the expression of ANXA2 [78] Regulating Wnt/β-catenin signaling pathway [80] findings also indicate that TRIM proteins regulate transcription by modifying chromatin. For instance, TRIM16 has been shown to increase histone acetylation and reactivate the transcription of retinoic acid receptor β2 (RARβ2) in retinoid-resistant breast and lung cancer cells [22].…”
Section: Trim16mentioning
confidence: 99%
“…This is consistent with previous reports that TRIM proteins can bind a protein to prevent its ubiquitination by another E3-ubiquitin ligase. For example, TRIM17 binds to BCL2A1 and prevents TRIM28-meidiated ubiquitination and degradation of BCL2A1 in melanoma cells [44]. Besides, TRIM24 is shown to inhibit the degradation of dysbindin in cardiomyocytes in a similar manner [45].…”
Section: Discussionmentioning
confidence: 99%